Mechanism for the Amorphisation of Diamond - Fairchild, B.; Rubanov, S.; Lau, D.; Robinson, M.; Suarez-Martinez, Irene; Marks, Nigel; Greentree, A.; McCulloch, D.; Prawer, S. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
The breakdown of the diamond lattice is explored by ion implantation and molecular dynamics simulations. We show that lattice breakdown is strain-driven, rather than damage-driven, and that the lattice persists until 16% of the atoms have been removed from their lattice sites.